Art Gallery Exhibiting : the Gallery as a vehicle for art. - Andriesse, Jan; Andriesse, Paul; Babias, Marius; Baer, Jo; Bauer, Ute Meta; Bischoff, Ulrich; Bloemheuvel, Marente; Boll, J.M.; Botha, Andries; Brüderlin, Markus; Buren, Daniel; Bustamante, Jean-Marc; et al. (Amsterdam : De Balie Amsterdam Galerie Paul Andriesse Amsterdam, 1996)
Andriesse, Jan ; Andriesse, Paul ; Anselmo, Giovanni ; Applebroog, Ida ; Asher, Michael ; Baer, Jo ; Beuys, Joseph ; Botha, Andries ; Buren, Daniel ; Bustamente, Jean-Marc ; Byars, James Lee ; Cadere, Andre ; Chamberlain, John ; Courbet, Gustave ; Denée, Michael ; Dijkstra, Rineke ; Dumas, Marlene ; Eichhorn, Maria ; van Elk, Ger ; Fairhurst, Angus ; Fortuyn/O'Brien ; Gober, Robert ; Goldin, Nan ; Graham, Dan ; Hohenbüchler, Christine ; Hohenbüchler, Irene ; Höller, Carsten ; Houshiary, Shirazeh ; Hundsbchler, Gottfried ; Jacobs, Henri ; Kirkeby, Per ; LeWitt, Sol ; Metzel, Olaf ; Mol, Pieter Laurens ; Orozco, Gabriel ; de Pavert, Jan van ; Penone, Giuseppe ; Ray, Charles ; Ruppersberg, Allen ; Serafijn, Q.S. ; Struth, Thomas ; Teniers, David ; Tillmans, Wolfgang ; de Vries, Jan Vredeman ; van Warmerdam, Marijke ; Welling, James ; Wilks, Steven
Biog. p. 217-218
boek